Novel hybrid treatments of textile wastewater by membrane oxidation reactor: Performance investigations, optimizations and efficiency comparisons - Aydiner, Coskun; Mert, Berna Kiril; Dogan, Esra Can; Yatmaz, Hüseyin Cengiz; Dagli, Sonmez; Aksu, Seyda; Tilki, Yasemin Melek (Elsevier Science Bv, 2019)
Feasible reclamation of industrial wastewaters by consuming less resource and time requires researchers to develop advanced and sophisticated solutions to meet today's versatile needs. In this respect, novel technological applications of hybrid membrane oxidation reactor (MOR) comprising of the Fenton or photo-Fenton enhanced ultrafiltration (FEUF and pFEUF), was demonstrated for treating textile washing wastewater. Their comparative hybrid performances were explored based on response surface analyses of Taguchi experimental designs that were optimized for maximized responses at minimum oxidant and acid consumptions. From eleven specific variables, those affecting the hybrid treatment performances at significant levels were found as H2O2 amount, process time, membrane type, Fe2+ concentration and temperature. The pFEUF treatment showed better and faster organics removal efficiency than by FEUF, and the UF process was seen to be more affected from changing operational conditions in pFEUF. Organic pollutants were oxidized by 56.6 +/- 8.7% degradation and 31.5 +/- 3.2% mineralization, while UF allowed a synergistic contribution to the hybrid MOR performance by 38.1 +/- 4.7% and 17.3 +/- 3.1%, respectively. Compared to simultaneous MOR and external UF after Fenton, sequential MOR was found as the best solution by an efficiency of 84.5% COD, 70.5% TOC, and 155.6 L/m(2).h. The effluents could be readily produced with quality suitable for directly discharging to the sewage infrastructure system resulting in a complete treatment. This study proved that the developed MOR techniques are technologically favorable for the treatment of industrial organic wastewaters due to high treatment performances and less resource, time and land needs. It can be finally declared that they can be used as rather attractive solutions for not only wastewater reclamation but also water recovery by further handling of their effluents. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Membrane oxidation reactor; Advanced oxidation processes; Submerged ultrafiltration; Textile wastewater; Taguchi experimental design; Response surface optimization